Organic Waste Management Strategy To Create Sustainable Circular Economy Using Swot and Qspm Model - Rahayu Rahayu; Putra Putra; Pujo Pujo (International Journal of Science and Environment (IJSE), 2024)
Organic waste management is crucial for sustainable climate change adaptation and mitigation. It supports a circular economy by recycling and repurposing waste, considering the entire product life cycle. This includes initiatives to recycle and repurpose organic waste as valuable resources, promoting a circular economy approach. The aim of the current study is to determine the best strategy for managing organic waste that can support a sustainable circular economy. SWOT analysis is a strategic planning tool based on strengths, weaknesses, opportunities, and threats. The QSPM assesses the attractiveness of alternative strategies for managing organic waste, evaluating external and internal factors that influence the organization. Further research is needed to promote sustainable circular economy principles.This research used the SWOT and QSPM Model to determine the best strategy for managing organic waste that can support a sustainable circular economy. The process involves analyzing internal and external factors of an organization, using the SWOT matrix to identify alternative strategies for programs or activities, and then using QSPM analysis to determine the sequence of these strategies and determine the best to lowest-value strategy outcomes, ensuring data input and decision-making. This study has been carried out in Garut, West Java, Indonesia in 2023. The study analyzes the progress of organic waste processing in Garut Regency using the SWOT-QSPM approach. The results provide insights into the organic waste management strategy for a sustainable circular economy, highlighting the importance of recycling organic waste into new products and supporting society's economy. The circular economy principle can be applied to the processing of organic waste by using BSF, a biological agent that can produce livestock feed and plant fertilizer, reducing the amount of organic waste sent to landfills. The strategies discovered can guide community programs, empowering those without fixed incomes to manage waste. The cultivation of BSF can be integrated with the farm, aiming to reduce poverty and unemployment rates, convert unused land into a community-managed waste management center, aiming to enhance production and income, educate and support the well-being of the community. The best practices for handling organic waste in Garut Regency to promote a sustainable circular economy have been determined by the SWOT-QSPM model. The chosen strategy prioritized 3 main aspects out of 7 alternative strategies : (1) Recruiting society members to manage organic waste processing centers as a routine activity and additional income through processing and cultivation programs; (2) Increasing productivity and scaling up the processing of organic waste to obtain diverse products with higher economic value; (3) Providing direct training and education on organic waste processing to the society to demonstrate the economic value that processed organic waste can generate.